Magnetoelastic resonance as a probe for exchange springs at antiferromagnet-ferromagnet interfaces - Seemann, K. M.; Gomonay, O.; Mokrousov, Y.; Horner, Andreas; Valencia, S.; Klamser, Pascal; Kronast, F.; Erb, Andreas; Hindmarch, A. T.; Wixforth, A.; Marrows, C. H.; Fischer, P. (Physical Review B, 2022)
In prototype ferromagnet-antiferromagnet interfaces we demonstrate that surface acoustic waves can be used to identify complex magnetic phases arising upon evolution of exchange springs in an applied field. Applying sub-GHz surface acoustic waves to study the domain structure of the ferromagnetic layer in exchange-biased bilayers of Ir20Mn80-Co60Fe20B20, we are able to associate the magnetoelastic resonance with the presence of the exchange spin-spirals in both the ferromagnetic and antiferromagnetic layer. Our findings offer a complementary, integrative insight into emergent magnetic materials for applications of noncollinear spin textures in view of low-energy-consumption spintronic devices.
CRIS-Team Scopus Importer:2023-03-27